A Dual‐Nanozyme‐Catalyzed Cascade Reactor for Enhanced Photodynamic Oncotherapy against Tumor Hypoxia. Issue 21 (8th September 2021) - Chen, Miaomiao; Song, Jitao; Zhu, Jialong; Hong, Gaobo; An, Jing; Feng, Erting; Peng, Xiaojun; Song, Fengling
Abstract: Tumor hypoxia is a typical characteristic of tumor microenvironment (TME), which seriously compromises the therapeutic effect of photodynamic therapy (PDT). The development of nanozymes with oxygen‐generation ability is a promising strategy to overcome the oxygen‐dependent of PDT but remained a great challenge. Herein, a dual‐nanozymes based cascade reactor HAMF is proposed to alleviate tumor hypoxia for enhanced PDT. The hollow mesoporous silica nanoparticles (HMSNs) are constructed as an excellent nanocarrier to load ultra‐small gold nanoparticles (Au NPs) and manganese dioxide (MnO2 ) shell via in situ reduction method, and further coordination with an efficient photosensitizer 4‐DCF‐MPYM (4‐FM), a thermally activated delayed fluorescence (TADF) fluorescein derivative. With the response to TME, MnO2 can catalyze endogenous H2 O2 into O2 and subsequently accelerating glucose oxidation by Au NPs to produce additional H2 O2, which is reversely used as the substrate for MnO2 ‐catalyzed reaction, thereby constantly producing singlet oxygen ( 1 O2 ) for enhanced PDT upon light irradiation. This work proposed a cascade reactor based on dual‐nanozyme to relieve tumor hypoxia for effective tumor suppression, which may enrich the application of multi‐nanozymes in biomedicine. Abstract : A tumor dual‐nanozyme‐catalyzed cascade reactor is fabricated for enhanced photodynamic oncotherapy against tumor hypoxia. In the cascaded reaction, endogenous hydrogen peroxide is transformed into oxygen, then oxygen is employed to produce additional hydrogen peroxide and singlet oxygen for enhanced photodynamic therapy upon light irradiation.